Occupational stress: an analysis of the causes - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig; Ahmad, Muhamad Hassan; Kasi, Arun (R.K.Sharma, Institute of Medico-Legal Publications, 2018)
Objective: This paper seeks to deliberate on the causes of occupational stress with reference to unmanageable workload, job insecurity, sexual harassment, workplace discrimination and employer’s unlawful conduct. Analysis: Excessive or unmanageable demands, insufficient support from co-workers and unsatisfactory working conditions may affect staff-motivation and productiveness. The main thing is to analyse that, the long-term stress or traumatic events at work may have affect the workers physically and psychologically. Method: Job uncertainty due to impending retrenchment, restructuring or management changes and hostile work environment could also give rise to occupational stress. Occupational stress often results in high dissatisfaction among the employees in terms of job mobility, burnout and poor work performance and less effective interpersonal relations at work. Findings: In the event of breach of this duty by the employer, apart from alleging constructive dismissal, the employee may be able to recover compensation for non-pecuniary loss such as mental distress or the effect of the dismissal on employee’s reputation or the chances of finding other employment. Result: The employer may also expose himself to a civil claim for negligence or a failure to provide a safe place of work. These causes of actions relate in deed to occupational or workplace stress, discussed in this article.